DEVELOPMENT OF OPERATING MODES IN MULTYPLAST BEDS - Заєць, Віктор Олександрович; Тимків, Дмитро Федорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This paper studies the flow of gas drilling wells and simultaneously opening them two potential sites for underground gas storage using perforations, with communication between horizons occur. As a result, the flow of gas. The ability to flow gas lingering above a lingering below the horizon determined by the difference of the initial reservoir pressure with the addition of pressure formed a pillar of gas that is directed from the upper horizon at the bottom. Several such methods is considered. One of them provides a qualitative assessment of the value of gas flows, depending on the frequency determining reservoir pressure in horyzontahznachnoyu extent. Measurements are carried out with a minimum gap of time. The whole period of uncontrolled gas flow is divided into time intervals that are characterized by the consistent implementation of reservoir pressure measurements in the upper horizon. This article, in addition to gas flows between the layers, exploring geo hydro dynamic control of the operation modes of the many underground gas storage reservoir. Travel time method used to investigate such regimes.